Hubungan Kecemasan dengan Kejadian Hipertensi Pada Lansia Di Puskesmas - Tiara Amanda, Salsa; Juhaeriah, Juju; Setya Roswendi, Achmad (Jurnal Keperawatan Komplementer Holistic, 2024)
Hypertension is one of the health problems for the elderly, the prevalence of hypertension in Padalarang Health Center reaches 1,947 people. Anxiety is one of the psychological factors that cause hypertension in the elderly. The purpose of this study was to determine the relationship between anxiety and the incidence of hypertension in the elderly at the Padalarang Health Center, West Bandung Regency. Method: This research design is an analytic survey with a cross sectional approach. The population in this study were elderly at Padalarang Health Center with a total of 100 respondents with purposive sampling technique. The instruments in this study used the Zung questionnaire and digital spignomanometer. Result: Univariate analysis using a frequency distribution table found that out of 100 respondents, 29 (29.0%) experienced severe anxiety and 70 (70.0%) respondents experienced hypertension. Bivariate analysis using the chi square test with the results of the study using the chi square statistical test obtained 31 respondents who felt normal anxiety as many as 16 people (51.6%) had hypertension, 40 respondents felt mild-moderate anxiety as many as 27 people (67.5%) had hypertension, 29 respondents felt severe anxiety as many as 27 people (93.1%) had hypertension, p value was 0.002 α (0.05) so there was a relationship between anxiety and the incidence of hypertension in the elderly at Padalarang Health Center, West Bandung Regency. Conclusion: In this study, it is hoped that preventive efforts can be made to minimize anxiety so that blood pressure in the elderly can be controlled with a spiritual approach.